Effects of color shade-net on the growth and yield quality of garlic in the lowlands area - Rachma, Izza Azkiya; Sulistyaningsih, Endang; Handayani, Valentina Dwi Suci (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
Garlic is a bulbous plant that grows and produces superb bulb yields in environments with temperatures between 15−25°C and humidity levels of 60−70%. A challenge in garlic growing in lowland areas is the suboptimal bulb growth caused by elevated air temperatures (23−37°C). Through experimentation with the 'Lumbu Putih' variety, predominantly cultivated at low elevations in Gunung Kidul Regency, the use of shade nets is anticipated to modify the microclimate, hence establishing optimal circumstances for garlic plant development. This research specifically targeted to identify the shade net colors that can alter the microclimate to optimize the development, productivity, and quality of garlic production. The study was performed in Logandeng Village, Playen District, Gunung Kidul Regency, Yogyakarta Special Region, at an elevation of approximately 215 meters above sea level. The treatments were organized according to a randomized complete block design (RCBD) including three levels: open land as a control, white shade nets, and black shade nets. Each treatment level comprised five replications organized as blocks. The data collected was analysed by analysis of variance (ANOVA) and the least significant difference (LSD) test at a significance threshold of 5%. The findings indicated that the shade net treatment enhanced the leaf count, leaf surface area, plant development rate, and dry weight per plant. The black shade net treatment yielded a superior quantity of cloves and an increased bulb density relative to the white shade net. According to the findings of structural equation modeling (SEM) study, garlic production is directly controlled by the yield component of 96.2% and indirectly affected by the growth component of 88.3%. The yield and growth component factors that generate direct and positive contributions, as indicated by the Stepwise Multiple Regression analysis, include total root length, plant dry weight, bulb diameter, and clove count.